Driving Digital Transformation in Small Banks With VRIO Analysis - Saur Simamora; Agus Rahayu; Puspo Dewi Dirgantari (School of Business, Bogor Agricultural University (SB-IPB), 2024)
This study evaluates a company's resources and capabilities to determine whether they can provide a sustainable competitive advantage on digital transformation. Using VRIO analysis, the study assesses the value, rarity, imitability, and organization of digital transformation in small banks. The results show that digital transformation is valuable for small banks but is familiar and relatively easy to imitate. Organizational support is critical for successful digital transformation in small banks. Small banks must leverage their strengths and adopt emerging technologies to remain competitive in the banking sector. Result of this study suggest that small banks can achieve competitive parity through a strategic focus on digital. Results on VRIO Analysis on PT. Bank XYZ that human resources, organizational structure, technology, product & services are competitively parity. However, capital resources, information systems, skills, and reputation are competitive advantages. Keywords: digital transformation, resource-based view, VRIO analysis, small banks